If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4/3x-7=2x-2
We move all terms to the left:
4/3x-7-(2x-2)=0
Domain of the equation: 3x!=0We get rid of parentheses
x!=0/3
x!=0
x∈R
4/3x-2x+2-7=0
We multiply all the terms by the denominator
-2x*3x+2*3x-7*3x+4=0
Wy multiply elements
-6x^2+6x-21x+4=0
We add all the numbers together, and all the variables
-6x^2-15x+4=0
a = -6; b = -15; c = +4;
Δ = b2-4ac
Δ = -152-4·(-6)·4
Δ = 321
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-15)-\sqrt{321}}{2*-6}=\frac{15-\sqrt{321}}{-12} $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-15)+\sqrt{321}}{2*-6}=\frac{15+\sqrt{321}}{-12} $
| 1/c=1/c1+1/c2+1/c3 | | 5(10x-26)=3-3(x+4) | | 35x-x^2=300 | | 65=(3.1415)•x | | b/86=49.1/72.6 | | r/15+2=4 | | 7(x+2)-(6x-5)=-22 | | 12.8*(x+35.5*2)=27x | | 51-3x=6 | | 12-y=8(y-3) | | 3x+5x-10=6x+8 | | 3b+12=16 | | 3x+5(x-2)=2(3x+4) | | 14x-6=2x-6 | | 3.1x^2+x-9.6x10^-2=0 | | 5(x+4)=4x+4 | | 7x=4=2x+3 | | 7x-4=2x+34 | | 7(2x–3)=5+4(x–2) | | 4+3w=-11 | | 9v+49=16v | | x+2(8)=6 | | 5r/12-8=14 | | .24x+2(.03+3)=12 | | 6+3b=7+2b | | 5y+2y=-24y | | 6=(2x-10)+3 | | X-180-x=44 | | (4x+12)-(4x+12/4)=48 | | X-90-x=8 | | n-9+n=1+4n | | (1/2)x=1.15 |